SERVICE QUALITY ON INTERNET BANKING - (:unkn) unknown (SPRINGER-VERLAG BERLIN, 2015)
This study was conducted to understand factors that would increase Internet banking usage. It was proposed that service quality, and convenience would increase satisfaction, which would then increases usage from organizational level. However from individual level, Internet self-efficacy and usage motives are the main factors necessary to increase usage.
Keywords: MULTIPLE-ITEM SCALE; ACCEPTANCE